EU policy towards Central and Eastern Europe: Development of pre-accession strategies - Ramūnas Vilpišauskas (Politologija, 1997)
The author continues the analysis started in the previous issue. The same analytical framework is used to discuss European Union's (EU's) policy towards the Central and Eastern European countries (CEECs) and its dynamics after the Copenhagen summit. The policy development was brought into a new stage during this period, and its main outcome was the pre-accession strategy designed for the CEECs that expressed the wish to become EU members. The main focus of the article is defining the main factors that seem to have influenced EU's policy and attempting to explain changes in the policy content. The Copenhagen Council decisions indicated the beginning of a long-term search for integration strategy on the part of EU decision-makers. This indicated that EU's policy towards CEECs started developing towards being outward-oriented and proactive rather than inward-oriented and reactive. This was reflected by the decisions of the Essen Council.